An Analysis of Islamic Moral Educational Values in The Film The Kite Runner - Rijal, Dzaky; Mardhiah, Ainal (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
This study aims to analyze the Islamic moral educational values contained in the film The Kite Runner, directed by Marc Forster and adapted from Khaled Hosseini’s novel. Employing a qualitative methodology combining library research and semiotic analysis, this research investigates key scenes, dialogues, and narratives within the film to identify and interpret moral values categorized into ethics toward God, self, and others. The findings reveal the film’s vivid portrayal of essential Islamic values such as monotheism (tauhid), trust in God (tawakkal), remembrance of God (dzikrullah), honesty (shiddiq), self-respect (iffah), patience (sabr), tolerance (tasamuh), compassion (rahmah), respect (ihtiram), and justice (adl). These values are embodied in the emotional and spiritual journeys of the characters, reflecting complex processes of moral and character development. The study underscores the film’s potential as a compelling audiovisual medium to foster ethical awareness and spiritual growth among learners. It contributes to expanding the repertoire of educational media that support character building within Islamic educational frameworks and offers valuable insights into the integration of global cinematic narratives in local moral education practices.